Soft X-ray absorption spectroscopy of Ar2 and ArNe dimers and small Ar clusters1. Issue 34 (14th September 2015) - Jabbari, Ghazal; Miteva, Tsveta; Stumpf, Vasili; Gokhberg, Kirill; O'Keeffe, Patrick; Ciavardini, Alessandra; Bolognesi, Paola; Coreno, Marcello; Avaldi, Lorenzo; Keshavarz, Elham; Ghandehari, Maryam; Tozihi, Manijeh; et al.
<x xml:space="preserve">Abstract</x> The X-ray absorption spectra of rare gas dimers and clusters have been studied experimentally and theoretically.